Case report: left atrial Myxoma causing elevated C-reactive protein, fatigue and fever, with literature review - Jake Cho; Steven Quach; Justin Reed; Omeni Osian (BMC Cardiovascular Disorders, 2020)
Abstract Background A cardiac myxoma in a young person may pose a diagnostic challenge as symptoms may be variable and the differential diagnosis is wide. The differential diagnosis can include rheumatic mitral valve disease, pulmonary hypertension, endocarditis, myocarditis and vasculitis. Case presentation This case report involves a 49 years old female with a 2.8 cm × 3.4 cm myxoma in the left atrium causing mitral valve obstruction. She presented with fatigue, fever of unknown origin, transient ischemic attack and shortness of breath. Prompt surgery is often recommended due to the risk of embolic complications or complete obstruction. Due to her symptoms, patient underwent successful cardiothoracic surgery to excise the myxoma within 2 weeks of confirmation by cardiac echocardiography. Conclusion This case also emphasizes the diagnostic challenge as symptoms may be variable, ranging from fatigue, fever and shortness of breath to transient ischemic attack and at worst, sudden cardiac death. In conclusion, if a cardiac mass is suspected, echocardiography should be performed early. Surgical resection is curative and recurrence rate is very rare in sporadic isolated myxomas, however, recurrence can be higher in genetic diseases associated with increased frequency of myxomas such as Carney complex. This subpopulation of patients may present further research opportunity to learn more about the perioperative management of patients with myxomas such as determining the optimal time to surgical intervention and decision to anticoagulate.